Destinations matter: The association between where older adults live and their travel behavior. Issue 1 (March 2015) - Chudyk, Anna M.; Winters, Meghan; Moniruzzaman, Md; Ashe, Maureen C.; Gould, Joanie Sims; McKay, Heather
Abstract The positive effect of physical activity in the prevention and treatment of many chronic diseases and age-related disabilities, such as mobility-disability, are widely accepted. Mobility is broadly defined as the ability of individuals to move themselves within community environments. These two concepts – physical activity and mobility – are closely linked and together contribute to older adults living healthy, independent lives. Neighborhood destinations may encourage mobility, as older adults typically leave their homes to travel to specific destinations. Thus, neighborhoods with a high prevalence of destinations may provide older adults an attractive opportunity to walk, instead of drive, and thereby obtain incidental physical activity. We know surprisingly little about the specific types of destinations older adults deem relevant and even less about destinations that support the mobility of older adults with low income. Accessible neighborhood destinations may be especially important to older adults with low income as they are more likely to walk as a primary travel mode. Conversely, this population may also be at increased risk of functional impairments that negatively affect their ability to walk. As a means to fill this information gap we aimed to better understand the mobility habits of older adults with low income. Thus, our specific objectives were to: (1) describe the types of destinations older adults with low income most commonly travel to in one week; and (2) determine the association between the prevalence of neighborhood destinations and the number of transportation walking trips these individuals make (average per day). We conducted a cross-sectional study of community-dwelling older adults with low income residing within Metro Vancouver, Canada. We assessed participant travel behavior (frequency, purpose, mode, destination) using seven-day travel diaries and measured the prevalence of neighborhood destinations using the Street Smart Walk Score. We also assessed participants' sociodemographic characteristics and mobility (physical function, car access, confidence walking). We used a negative binomial model to determine the association between Street Smart Walk Score and number of transportation walking trips (average per day). Our sample was comprised of 150 participants (median age 74 years; 51 men) from who we acquired at least one day of travel diary data (range=1–7 days). Participants made three trips per day (2, 5; median P25, P75) and travelled to six different destination types per week (5, 9; median P25, P75). Destinations most relevant to older adults were grocery stores, malls, and restaurants/cafés. Each 10-point increase in Street Smart Walk Score was associated with a 20% increase in the number of transportation walking trips (average per day, incidence rate ratio=1.20, 95% CI=1.12, 1.29). Our findings provide preliminary evidence regarding destinations that may be most relevant to older adults. They also suggest that the prevalence of these neighborhood destinations may encourage walking. As we approach a new era of healthy city benchmarks, our findings guide policy makers and developers to retrofit and develop communities that support the mobility, health, and independence of older adults.